Producción académica cualitativa sobre el sentido del trabajo 2010-2023 en Latinoamérica - Bringas-Acevedo, José Eduardo (2023)
This study used a qualitative approach in the form of a systematic review, specifically using concept maps to analyze research conducted by Latin American authors on the subject of the meaning of work. The analysis covered research studies published on academic databases from 2010 to 2023. The primary aim of this study was to identify common themes and theoretical frameworks derived from the body of research. Another aim of this study was to draw attention to the limitations of existing research and to explore innovative approaches to the understanding of human talent. The study also discussed future research pathways in the field of the meaning of work. The study findings revealed that there is a significant number of qualitative-based publications that address current issues related to traditional and non-traditional employee groups. Even so, this study revealed a key area to further develop: qualitative studies focused on the overlap of artificial intelligence, automation and related technologies destined to affect both the nature of work and human capital management, since these emerging technological trends will invariably influence the way in which employees think about work, thereby affecting how they regard its sense and importance.